A simulation study on the behavior of allelic richness and inbreeding coefficient over generations in fragmented populations of tree species - Valdir Marcos Stefenon; Leonardo Severo da Costa (Annals of Forest Research, 2012)
Computer simulations were employed in this study aiming to understand the effects of repeated cycles of inbred mating in isolated populations of tree species with different effective sizes and over up to 1000 generations. The results revealed a susceptibility of allelic richness to both, population size and repeated generations under inbred mating and a low but significant increase of the inbreeding coefficient over generations in populations with 50 and 100 plants, but not in populations with 500 and 1000 individuals. The loss of alleles occurred throughout all generations and was largely influenced by the population size. The most outstanding increase in the inbreeding coefficient occurred from the initial generation to the 5th generation, independent of the population size. The comparison of simulated results with data obtained from a field studie corroborated the hy pothesis that isolated populations tend to more drastically suffer with loss of alleles and increase of inbreeding coefficient, wh ile continuous forests, with effective production of fertile seeds and regeneration of seedlings, are inclined to preserve comparatively higher allelic richness and lower inbreeding coefficient over generations. In general, the results obtained highlight the importance of special care in selecting ESUs and preserving isolated populations, towards the conservation of forest genetic resources and adapatedness preservation